THE SYSTEM OF INDICATORS FOR EVALUATING THE ECONOMIC EFFICIENCY OF AGRICULTURAL PRODUCTION (American Journal of Interdisciplinary Research and Development, 2022)
The article analyzes the system of indicators for evaluating the economic efficiency of agricultural production. In addition, indicators for evaluating the economic efficiency of agricultural production in the regions have been developed.